Hepatoid carcinoma and related entities of the extrahepatic bile duct: A clinicopathological study of four cases. Issue 6 (26th April 2022) - Okura, Keisuke; Esaki, Minoru; Nara, Satoshi; Ban, Daisuke; Takamoto, Takeshi; Shimada, Kazuaki; Hiraoka, Nobuyoshi
Abstract: Hepatoid carcinoma or related entities (HPC/RTs) are extremely rare, especially in the extrahepatic bile duct (EHBD). Only a few case reports have been published. We analyzed the clinicopathological features of HPCs/RTs in EHBD. HPC/RT of extrahepatic cholangiocarcinoma (eCCA) cases were selected based on the histological characteristics and immunohistochemical detection of spalt‐like transcription factor 4 (SALL4) and/or alpha‐fetoprotein (AFP). Four HPC/RT cases arose in the distal but not in the perihilar EHBD. The four patients with HPC/RT included one female and three males with a median age of 77 years. There are various macroscopic types of HPC/RT. The predominant histological features were two solid‐type carcinomas that mimicked hepatocellular carcinoma and two well‐differentiated tubular adenocarcinomas. Immunohistochemically, SALL4 and glypican‐3 were expressed in all cases, and AFP was expressed in one case. Cancer cell phenotypes included intestinal, pancreatobiliary, and mixed pancreatobiliary and intestinal types. Focal neuroendocrine differentiation and severe perineural and lymphovascular invasions were also observed. HPC/RT recurred in two patients within 2 years, and one patient died 13 months postoperatively. It is suggested that the HPC/RT of EHBD shares common characteristics with HPC/RT arising in various organs, and has some unique characteristics. HPC/RT of EHBD might be more aggressive than conventional eCCA.